Effects of contrast material on computed tomographic measurements of lung volumes in patients with acute lung injury - Bouhemad, Bélaid; Puybasset, L.; Coriat, P.; Roussat, M. O.; Goldstein, I.; Nieszkowska, A.; Richecoeur, Jack; Lu, Qin; Malbouisson, Luiz M.; Cluzel, Philippe; Rouby, Jean-Jacques; Gusman, P. [UNESP]; et al. (Springer Nature, 2003)
Background. Intravenous injection of contrast material is routinely performed in order to differentiate nonaerated lung parenchyma from pleural effusion in critically ill patients undergoing thoracic computed tomography (CT). The aim of the present study was to evaluate the effects of contrast material on CT measurement of lung volumes in 14 patients with acute lung injury. Method. A spiral thoracic CT scan, consisting of contiguous axial sections of 10 mm thickness, was performed from the apex to the diaphragm at end-expiration both before and 30 s (group 1; n=7) or 15 min (group 2; n=7) after injection of 80 ml contrast material. Volumes of gas and tissue, and volumic distribution of CT attenuations were measured before and after injection using specially designed software (Lungview®; Institut National des Télécommunications, Evry, France). The maximal artifactual increase in lung tissue resulting from a hypothetical leakage within the lung of the 80 ml contrast material was calculated. Results. Injection of contrast material significantly increased the apparent volume of lung tissue by 83 ± 57 ml in group 1 and 102 ± 80 ml in group 2, whereas the corresponding maximal artifactual increases in lung tissue were 42 ± 52 ml and 31 ± 18 ml. Conclusion. Because systematic injection of contrast material increases the amount of extravascular lung water in patients with acute lung injury, it seems prudent to avoid this procedure in critically ill patients undergoing a thoracic CT scan and to reserve its use for specific indications.
Keywords: Acute lung injury; Contrast material; Lung volumes; Thoracic computed tomography scan; contrast medium; adult; aged; artifact; attenuation; clinical article; computer assisted tomography; computer program; contrast enhancement; controlled study; critical illness; dose response; expiratory flow; female; human; hypothesis; lung extravascular fluid; lung injury; lung parenchyma; lung volume; male; measurement; pleura effusion; priority journal; review; treatment indication; Adult; Aged; Aged, 80 and over; Contrast Media; Extravascular Lung Water; Female; Humans; Injections, Intravenous; Lung Volume Measurements; Male; Middle Aged; Radiographic Image Enhancement; Respiratory Distress Syndrome, Adult; Tomography, Spiral Computed